Flower visitors of Eriope blanchetii (Benth.)Harley (Labiatae) in Abaeté coastal sand dunes, Salvador, Bahia - Silva, Fabiana O.; Viana, Blandina F. (SITIENTIBUS série Ciências Biológicas, 2002)
This work investigates the temporal variation in composition and activity of floral visitors of Eriope blanchetii (Benth.)Harley, emphasizing the effect of the duration of the flowering period and its intensity upon frequency of visits by the dominant species. The observations were conducted from October 1999 to October 2000 on a wild population of E. blanchetii located at Área de Proteção Ambiental das Lagoas e Dunas do Abaeté - APA (1206’S, 38021’W), in Salvador, state of Bahia. In total, 354 visiting insects were collected on the flowers and the Hymenoptera group predominated. The solitary bees were the most representative group (85%) of all visitors caught. Other insect visitors (15%) included Hymenoptera such as Formicidae (4%) and Vespoidea (4.5%) and also Lepidoptera (4.25%), Diptera (1.7%), and Coleoptera (0.3%). Xylocopa cearensis Ducke, 1910 (28.32%), Pseudoaugochloropsis pandora Smith, 1853 (15.30%), and Colletes petropolitanus Della Torre, 1896 (9.39%) were the predominant species. They were active during all day long, coinciding with anthesis. The number of visiting bees was higher in plants with longer flowering period and which produced numerous flowers. The diversity and number of flower visiting bees was greater during the flowering peaks, while the other insects were more abundant and diverse during low flowering.